UV and Visible Spectrophotometric Methods for the Determination of Roxatidine Acetate Hydrochloride in Pharmaceutical Formulations - Seshagiri Rao, J.V.L.N.; Rama Prasad, L.A.; Vijayasree, V.; Srinivasa Rao, Y. (Asian Journal of Chemistry, 2010)
Two simple and reproducible spectrophotometric methods have been developed for the estimation of roxatidine acetate hydrochloride. In the UV region, the drug showed maximum absorption at 208 nm in distilled water. In the proposed visible spectrophotometric method, the drug is made to react with Folin-Ciocalteu (FC) reagent under alkaline conditions, when it forms a blue coloured chromogen having absorption maximum at 750 nm. These methods obey Beer's law in the concentration range 5-40 μg/mL and 25-100 μg/mL respectively. The methods are statistically evaluated for accuracy and precision.